Circulating miRNAs: cell–cell communication function? - Turchinovich, Andrey; Samatov, Timur R.; Tonevitsky, Alexander G.; Burwinkel, Barbara (Frontiers in Genetics, 2013)
Nuclease resistant extracellular miRNAs have been found in all known biological fluids. The biological function of extracellular miRNAs remains questionable; however, strong evidence suggests that these miRNAs can be more than just byproducts of cellular activity. Some extracellular miRNA species might carry cell–cell signaling function during various physiological and pathological processes. In this review, we discuss the state-of-the-art in the field of intercellular miRNA transport and highlight current theories regarding the origin and the biological function of extracellular miRNAs.